Prevalensi Malaria Klinis Dan Positif Plasmodium spp. Berdasarkan Mass Blood Survey - Budi Santoso (Loka Litbang Kesehatan Pangandaran, 2010)
In West South East Maluku district, malaria diagnosis was determined mostly based on sufferer clinical symptom. Diagnose malaria by clinical symptom have much weaknesses compared to laboratory result, because a lot of other infection disease which has similar symptom to malaria. This fact is the reason of this research done, that amount of positive malaria based on clinical symptom will differ from the circumstance in fact. The aim of this research was to know prevalence of clinical malaria and positive malaria Plasmodium spp among the people who came to examination site. Research has been done by check parasite Plasmodium spp. at the patient blood sample either who has fever symptom or no symptom at 10 villages in West South East Maluku district. The research was resultedthat prevalence of fever clinical symptom is 275.722 persons per 1,000 peoples; prevalence of positive Plasmodium spp. is 273.005 persons per 1,000 peoples. This result was showing that rate malaria prevalence is high and named high incidence area or high caseincidence.